Preparation and Characterization of Paracetamol Solid Dispersions Using Opened Ring PVP and PEG 4000 - hossein asgarirad; ali farmoudeh; anahita rezaeiroshan; mohammadjavad rajaei (Fasa University of Medical Sciences, 2019)
Background & Objective: Solid dispersions (SDs) have been traditionally used as an effective method for improving the dissolution properties and bioavailability of poorly water-soluble drugs. The aim of this study was to improve the solubility and dissolution rate of paracetamol by SD technique. Materials & methods: The prepared SDs were evaluated by saturation solubility test, In-vitro drug release test, differential scanning calorimetry (DSC), Fourier transform infrared spectroscopy (FTIR), and scanning electron microscopy (SEM). Results: The prepared SDs exhibited a statistically significant increase in the solubility of paracetamol compared to that of the free drug (p < 0.05). After 15 min SD tablets had an enhanced cumulative drug release compared to tablets of the free drug (p < 0.05). FTIR study revealed that paracetamol was stable in polymeric dispersions. DSC and SEM microscopy showed that the drugs crystallinity was decreased during the preparation process (amorphous crystal formation). Conclusion: The FTIR spectroscopic test revealed the presence of intermolecular hydrogen bonding between paracetamol and the polymers in the SDs, which could increase the aqueous solubility of the drug. The DSC analysis indicated that the drug was in the amorphous state when dispersed in the polymers. Dissolution studies indicated that the dissolution rates were markedly increased in the SDs compared with those of paracetamol alone, and Better results were obtained with PVP K25.